(untitled) (Revista Brasileira de Ciências Farmacêuticas, 2002)
The treatment of critically-ill patients has aroused great interest during the last years. The nutrition support has an important role for these patients, seeking to prevent the protein-energy malnutrition and to evaluate and determine the appropriate nutrient requeriments. Some diets are available, however, immune-stimulating diets wish arginine, omega-3 fatty acids, nucleotides and glutamine have been used in an effort to decrease infectious complications, but their therapeutic advantages are still being debated.